KESIAPAN PENERAPAN KELAS RAWAT INAP STANDAR (KRIS) DI RUMAH SAKIT DI INDONESIA: SYSTEMATIC REVIEW - Aini, Rafika; Aulia, Mirza; Bhagas Yudhanto, Satrio; Handam Dewi, Siti; Fitriani, Yessy (Ensiklopedia of Journal, 2024)
The country has a responsibility to ensure that its citizens have access to adequate healthcare services, according to various health concepts and definitions. The purpose of this research is to determine the readiness of hospitals in implementing standard inpatient care classes. This study is a systematic review. The data sources for this research were obtained through literature searches on the internet using Google Scholar, Portal Garuda, and Open Knowledge Map. After screening, five journals were found to meet the criteria. The research results found that hospitals have undergone transformation to implement the Standard Inpatient Class (KRIS). However, there are still challenges and issues hindering the achievement of the KRIS target. One influencing factor is the deficit in BPJS Health due to arrears in contributions by certain participants. As a result, the standardization of care classes cannot be uniformly implemented. Additionally, the lack of achievement in implementing the KRIS JKN policy is due to some hospitals not meeting the 12 criteria for KRIS JKN implementation.Keywords: Standard Inpatient Class, Readiness, Implementation